Information and communication technologies in higher education - Martínez-Sánchez, Lina María (2023)
ICTs have boosted the education of students at different levels of education. The aim of this article is to present a review of Information and Communication Technologies in the field of higher education, in order to establish their advantages and disadvantages as a new learning method. To develop this review, a literature search was conducted in databases such as WoS, Education-Research, Lilacs and Redalyc, by selecting keywords such as "education", "technology" and "learning". After identifying the studies of interest, titles, abstracts, and keywords were read to verify their correlation with the review, thus delimiting a final sample of N=30. ICTs have managed to leave behind the traditional teacher-centered learning to give way to a learning process where the student is the protagonist. Finally, it can be concluded that among the balance of advantages and disadvantages, if something is clear, it is that ICTs have revolutionized education, teaching, learning, and the classroom within the educational context, which is why society must be prepared to transform.